Bioprospecting microalgae with the capacity for inducing calcium carbonate biomineral precipitation - Arumugam, Kavithraashree; Mohamad, Rosfarizan; Ashari, Siti Efliza; Tan, Joo Shun; Mohamed, Mohd Shamzi (John Wiley and Sons, 2022)
Calcium carbonate precipitation is a form of sedimentary carbonate which occurs naturally in an ecosystem saturated with calcium ions and prompted by a wide assortment of microorganisms through various biological processes. The phenomenon, also known as “Microbially Induced Calcium Carbonate Precipitation” (MICP), may find the characteristics of its by-product biomineral to be a promising alternative for conventional cement. Several microalgae species can produce cementitious CaCO3 deposits, which are permanently removed as solid crystal upon achieving suitable conditions for precipitation. This study assessed a total of eight microalgae for their biomineralization capability in calcification media containing 12 mM of calcium chloride dihydrate and 0.18 to 5.0 mM of sodium bicarbonate by analyzing the profiles of cell growth, pH, calcium and bicarbonate ions concentration, alkalinity, and saturation index. Among the microalgae tested, Synechocystis sp. ATCC 27178 cultured in BG-11 medium with 5.0 mM of NaHCO3 had shown the highest calcium ions removal rate (0.70 mM/day), followed by Chlorella vulgaris (0.40 mM/day). The morphology of CaCO3 crystals precipitated from these microalgae was analyzed via scanning electron microscopy (SEM) coupled with energy dispersive X-ray (EDX). The elucidation of the crystal polymorph as calcite was then confirmed through X-ray diffraction analysis.